Between work responsibilities and family obligations: a study on the management of work-life integration among academics - Dzurizah Ibrahim; Kee.Y. Sabariah Kee Mohd Yussof; Rose Patsy Tibok (Medwell Journals, 2016)
Between work responsibilities and family obligations: A study on the management of work-life integration among academics. The management of work-life integration is an important element in the career of any individual, regardless of gender. In this era of globalisation, work and life integration has become a priority not only for dual-career women but also for male workers. A study conducted among the academic workforce in two public universities in Sabah, Malaysia to explore the extent of the perceived importance of managing work-life integration in fulfilling responsibilities at work and family obligations, found similar perceptions in both male and female workers. It is therefore contingent that organisations provide work-life integration programmes to assist their workforce in creating, managing and sustaining a more effective lifestyle. The workforce as organisational assets should be sustained with continuous encouragement and motivation to ensure their dedication and commitment to both their career and religious, family and societal obligations.